Hierarchical Ti3C2 MXene/Zn3In2S6 Schottky junction for efficient visible-light-driven Cr(VI) photoreduction. Issue 8 (15th April 2022) - Yin, Hongfei; Yuan, Chunyu; Lv, Huijun; Zhang, Kaiyue; Chen, Xue; Zhang, Yongzheng
Abstract: Environmental crisis aroused from the Cr(VI)-containing wastewater has received much attention, due to the cancer-causing and mutagenic feature of Cr(VI). Photocatalytic technology has been considered to be a favorable contestant for coping with Cr(VI)-containing effluent. In this study, Ti3 C2 MXene/Zn3 In2 S6 Schottky junctions with different content of Ti3 C2 MXene were prepared for Cr(VI) photoreduction. The inherent physical and photoelectrochemical characters of the obtained Ti3 C2 MXene/Zn3 In2 S6 Schottky junctions were fully characterized. Compared with the pure Zn3 In2 S6, all the nanocomposites showed enhanced photocatalytic performance, the apparent kinetic constant of the optimized sample was 3.17 times the height of the Zn3 In2 S6 . The improved photoreduction performance largely originated from the effectual separation and transfer of the photoexcited charge carriers. In the meantime, the deleterious role of superoxide radicals for Cr(VI) photoreduction was confirmed. It is anticipated this research can deliver a new-fangled vision for constructing efficient photocatalyst for Cr(VI) photoreduction.